Practices of Healthcare Workers regarding Infection Prevention in Bale Zone Hospitals, Southeast Ethiopia - Demisu Zenbaba; Biniyam Sahiledengle; Daniel Bogale (Advances in Public Health)
Introduction. In Ethiopia, infection prevention to protect patients, healthcare workers, and visitors from healthcare-acquired infections is one of a number of nationwide transformational initiatives to ensure the provision of quality healthcare services. The aim of this research was to assess the practice of healthcare workers regarding infection prevention and its associated factors in Bale zone Hospitals. Methods. A cross-sectional study targeted 402 healthcare workers using simple random sampling to learn about their practices related to infection prevention. Data were collected in interviews using pretested, structured questionnaires. Returned questionnaires were checked for completeness and then data were entered into a database and analyzed using SPSS Version 20. Adjusted odd ratio (AOR) with a 95% confidence interval was calculated to determine the strength of association, and variables with a p value <0.05 in the final model were considered as statistically significant. Results. Three hundred ninety-four healthcare workers participated in the study. Of these; 145 (36.8%, 95% CI 32, 42%) of them were found to have self-reported good infection prevention practice. Good knowledge towards infection prevention (AOR = 1.84, 95% CI 1.02, 3.31), availability of personal protective equipment (AOR = 1.96, 95% CI 1.16, 3.32), and water (AOR = 4.42, 95% 2.66, 7.34) at workplace were found to have a statistically significant association with healthcare workers self-reported good infection prevention practices. Conclusions. In this study, slightly more than one-third of the healthcare workers reported to have good infection prevention practice. Good knowledge towards infection prevention, working in departments, availability of personal protective equipment, and water at work place were found to have statistically significant association with self-reported good infection prevention practices.